If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -16 + 3x = x Solving -16 + 3x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -16 + 3x + -1x = x + -1x Combine like terms: 3x + -1x = 2x -16 + 2x = x + -1x Combine like terms: x + -1x = 0 -16 + 2x = 0 Add '16' to each side of the equation. -16 + 16 + 2x = 0 + 16 Combine like terms: -16 + 16 = 0 0 + 2x = 0 + 16 2x = 0 + 16 Combine like terms: 0 + 16 = 16 2x = 16 Divide each side by '2'. x = 8 Simplifying x = 8
| (x-5)(5-6)=2 | | 378=6-6(8b-6) | | (4a+5)(4a+5)(4a+5)= | | -6.1a=74.42 | | -9.3=g-1.7 | | =x^2-10x+425 | | /2+x/5=1 | | 16x^4-16x^2+3=0 | | 3x+5=-2(x-5) | | 8r^2+23r=36 | | 9=-2-y | | 34x-13=55 | | 16a+2b=4 | | -15=5m^2+28m | | Y=8x^2+2x-3 | | -1x+3=-8 | | n+n+1+n+2=54 | | -6-2x=10-8 | | .25x+8=.62x+2 | | 15/(8n-32) | | 11x-33=8x+0 | | 2x^2-7x-70=3x | | 5p+2=4p-9 | | (-18)+q=5 | | 2t^2+5=2t^2+1 | | n+n+1+n+1=54 | | 15/8n-32 | | -5.9=k/3 | | 25m^2+2=3 | | 7-3x=5x+14 | | 10x-50=25 | | 3x-6x^2/x^3 |